Relevansi Konsep Harta Bersama Dalam Kompilasi Hukum Islam Dengan Hukum Islam - Paisal, Paisal; Winario, Mohd; Hidayat, Hidayat; Nongliasma, Nongliasma (Journal of Legal Sustainability, 2025)
The concept of joint marital property is an important aspect of family law in Indonesia as regulated in the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI). The existence of this concept is often debated in terms of its relevance to Islamic law, considering that classical fiqh does not explicitly recognize the term joint property in marriage. This study aims to analyze the relevance of the concept of joint property in the KHI to the principles of Islamic law, as well as to examine the normative and philosophical foundations of its application. The research employs a library research method with a juridical-normative approach, analyzing sources of Islamic law, statutory regulations, and the opinions of scholars and legal experts. The results indicate that although the concept of joint property is not textually mentioned in classical fiqh, its substance is consistent with the principles of justice (‘adl), public interest (maslahah), and cooperation (syirkah) in Islam. Therefore, the concept of joint property in the KHI can be viewed as a form of contextual ijtihad that is relevant to Islamic legal values and the needs of Indonesian Muslim society.